2015
DOI: 10.3109/02713683.2015.1039651
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes in Pseudoexfoliation Syndrome Evaluated with Spectral Domain Optical Coherence Tomography

Abstract: In PEX syndrome, similar decreases of the GCC and NFL occurred, and a high correlation existed between the two. Therefore, GCC can potentially be used to detect the early stages of PEX glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
2
13
0
1
Order By: Relevance
“…It is one of the commonest causes of secondary open angle glaucoma and in the Blue Mountains Eye study, patients with PEX in either eye have a two to threefold higher risk of open angle glaucoma 11,12. Although blindness is the most feared outcome, there is growing evidence that even mild visual field loss may have an adverse effect on quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is one of the commonest causes of secondary open angle glaucoma and in the Blue Mountains Eye study, patients with PEX in either eye have a two to threefold higher risk of open angle glaucoma 11,12. Although blindness is the most feared outcome, there is growing evidence that even mild visual field loss may have an adverse effect on quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the work done on measurement of RNFL thickness in PXF syndrome without glaucoma using different OCT machines revealed thinner mean global peripapillary RNFL in eyes with PXF as compared to control group with some variations in quadrantic measurements that may be attributed to variation in age, sample size, ethnicity and type of OCT machine used 2,3,6,12. Ozge et al in their study compared RNFL thickness in eyes with PXF glaucoma, PXF syndrome and healthy controls 15.…”
Section: Discussionmentioning
confidence: 99%
“…For the other 3 quadrants, the significance of RNFL thickness reduction varied by OCT type. These variations in measurements may be attributable to the small sample size, different ethnicities and possible systemic diseases of the study participants, and the susceptibility of each quadrant to "thinning" or "cell damage" [7,11,13,33] .…”
Section: Discussionmentioning
confidence: 99%
“…In our study we found that average, superior and nasal RNFL thickness thinner than control group. In that study they reported that the superior and total macular nerve fiber layer thickness, superior total GCC and inner plexiform layer thickness, superior, inner and total GCC thickness were thinner than control subjects [31]. In our study, we just compared mean and minimum GCC thickness and we detected significant difference in these GCC values.…”
Section: Rnfl (µ) Pexsmentioning
confidence: 76%
“…The first study about this subject was that Eltutar et al [31] compared pseudoexfoliation syndrome with control subjects. Macular NFL, ganglion cell layer and inner plexiform layer, total peripapillary nerve fiber layer and ONH parameters were compared.…”
Section: Rnfl (µ) Pexsmentioning
confidence: 99%